2016
DOI: 10.12957/reuerj.2016.21937
|View full text |Cite
|
Sign up to set email alerts
|

Custos do programa de Gerenciamento de Doentes Crônicos de uma Operadora de Saúde

Abstract: RESUMOObjetivo: analisar a estratégia de contenção de custos por múltiplas internações evitáveis de um Programa de Gerenciamento de Doentes Crônicos (GDC), desde sua implantação, em uma operadora de saúde. Método: estudo retrospectivo, abordagem quantitativa em que foi realizado um levantamento dos dados obtidos através do acompanhamento dos 243 pacientes assistidos pelo programa de 2009 a 2012. Aprovado pelo CEP sob o CAAE: 34525614.8.0000.5285. Resultados: com relação às patologias de base, a maioria dos pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
0
0
1
Order By: Relevance
“…4 Healthcare costs have been increasing exponentially, causing the scarcity of available resources, which makes it necessary to acquire managerial knowledge that contributes to cost restriction and efficient resource allocation. [5][6] In the literature, studies involving costs and waste show that according to health professionals, the greatest source of waste is related to material resources, which generates an estimated annual cost of approximately 479 million reais. The waste related to these resources can occur from the purchase of stocks of questionable quantity and quality to the use of inadequate form and quantity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Healthcare costs have been increasing exponentially, causing the scarcity of available resources, which makes it necessary to acquire managerial knowledge that contributes to cost restriction and efficient resource allocation. [5][6] In the literature, studies involving costs and waste show that according to health professionals, the greatest source of waste is related to material resources, which generates an estimated annual cost of approximately 479 million reais. The waste related to these resources can occur from the purchase of stocks of questionable quantity and quality to the use of inadequate form and quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, scholars have been indicating the use of management tools to change the reality of waste in hospitals and to maintain their economic viability. [5][6][7] The inefficiency of the managerial process in healthcare, administrative incapacity, and lack of knowledge about costs of procedures, inputs, and equipment may compromise institutional finances and increase avoidable costs. 8 Since 1982, the World Health Organization (WHO) has indicated that nurses have the potential to ensure cost-effective care.…”
Section: Introductionmentioning
confidence: 99%
“…A partir deste cenário, faz-se necessário que os profissionais adquiram maiores conhecimentos sobre custos e sobre medidas para equilibrá-los. Para tanto, as preocupações têm se voltado para apuração e controle dos custos hospitalares e também para medidas visando sua contenção enfocando o desperdício, que vem sendo uma das principais fontes de gastos dentro do setor (3)(4)(5)(6) .…”
Section: Introdução Ounclassified